2008
DOI: 10.13031/2013.25141
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Aerial Delivery Systems for Spray Deposition and Efficacy against Sweet Potato Whitefly on Cotton

Abstract: Sweet potato whiteflies (SWF), Bemisia argentifolii, live on the bottom surface of cotton leaves. Except crawlers, nymphal stages of the insect will not move about to contact insecticides. Aerial sprays to suppress SWF require improved application techniques designed to increase spray deposition and penetration to the lower layers of cotton canopy. Using Rotary atomizers, Winglets, and Trumpet nozzles with combination of air speed and boom heights, fenpropathrin 2.4E + acephate 90S at 0.22 + 0.56 kg active ing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Leaf samples for immature whiteflies were collected 3 days after sprays were applied, and sent via overnight mail to USDA Laboratory, College Station, TX, for processing. Populations of whitefly eggs and large nymphs were counted according to leaf‐plug sampling methods described earlier 13, 14…”
Section: Methodsmentioning
confidence: 99%
“…Leaf samples for immature whiteflies were collected 3 days after sprays were applied, and sent via overnight mail to USDA Laboratory, College Station, TX, for processing. Populations of whitefly eggs and large nymphs were counted according to leaf‐plug sampling methods described earlier 13, 14…”
Section: Methodsmentioning
confidence: 99%
“…A water‐sensitive spray card (26 by 76 mm; Syngenta, Basel, Switzerland) was placed in a horizontal position immediately adjacent to each cotton plant. These yellow cards turn blue when in contact with water, and have been used mainly in research projects to obtain quantitative data on spray coverage 17, 24, 27, 35. A spray bottle (947 mL; Sprayco, Detroit, MI) containing one of the miticide solutions was held vertically above the cotton plant and water‐sensitive spray card, and the distance was varied to allow spray coverage to vary.…”
Section: Methodsmentioning
confidence: 99%
“…Many important factors affect the obtained spray coverage when pesticides are applied in field crops, including type of spray nozzle,15–17 use of adjuvants,17–21 type of carrier,22 spray volume,15–17, 23 type of spray application24, 25 and timing of pesticide applications 25, 26. Spray coverage studies involving water‐sensitive spray cards have shown that it is not uncommon, especially with aerial fixed‐wing applications, for leaf deposition to be below 1% in the lower portion of a sprayed crop canopy 24, 25, 27. Several studies have shown how weather conditions, in particular, can markedly influence the actual coverage when pesticides are applied 25, 28…”
Section: Introductionmentioning
confidence: 99%
“…On average, the bottom portion of the canopy received about half the spray coverage of the top portion, and only one of the nine applications provided over 10% average spray coverage in the bottom portion of the canopy. Published spray coverage studies using water sensitive spray cards have shown that it is not uncommon, especially with aerial spray applications, to obtain spray coverages below 1% [15][16][17].…”
Section: Control Measures Of Insecticide Applicationsmentioning
confidence: 99%